RANCANG BANGUN SISTEM KELISTRIKAN PADA MESIN PELONTAR PAKAN IKAN OTOMATIS BERBASIS ARDUINO - Prasetyo, Indra Dwi; Ramdani, Rizki (Jurnal Mahasiswa Terapan, 2024)
This research focuses on designing and developing the electrical system for an automatic fish feed dispenser machine basen on Arduino. The system is designed to enhance efficiency an accuracy in the automatic feeding of fish, which is crcial in aquaculture. In this system, Arduino is used as the main microcontroller to control the entire mechanism, from time management to motor control. The designed electrical system includes the power supply, AC motor control, and sensor that support automated operations. Testing shows that the system operates as expected, with feed being distribusted evenly and on time according to the programmed schedule. The result of this research are expected to provide a practical solution  for more efficient and automated fish farming.